2018
DOI: 10.1097/tp.0000000000002009
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Renal Cell Cancer After Renal Transplantation in a Multicenter French Cohort

Abstract: Recurrences of clear cell RCC are not uncommon after kidney transplantation and are associated with very poor prognoses. These results should be considered before listing patients with a history of renal cancer for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
18
1
3
Order By: Relevance
“…Twenty-one articles were case reports and three articles were not in English. Thus, 22 cohort studies [11,12,13,14,15,16,17,18,19,20,23,28,29,30,31,32,33,34,35,36,38,39] with a total of 320,190 KTx patients were enrolled. The literature retrieval, review, and selection process are demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one articles were case reports and three articles were not in English. Thus, 22 cohort studies [11,12,13,14,15,16,17,18,19,20,23,28,29,30,31,32,33,34,35,36,38,39] with a total of 320,190 KTx patients were enrolled. The literature retrieval, review, and selection process are demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Despite screening for RCC among KTx candidates, de novo RCC has been reported among KTx patients in both native kidneys [11,12,13,14,15,16,17,18], and transplanted kidneys [17,19,20]. However, the incidence and incidence trends of RCC among KTx patients remain unclear [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Because of immunosuppressive drugs use, the incidence of malignancies has increased significantly after renal transplantation. [4] It is generally believed that there are 3 main sources of tumor after renal transplantation: primary tumor after renal transplantation; tumor recurrence before renal transplantation; tumor derived from donor kidney. Urinary tract tumor especially urothelial carcinoma, is the main type of tumor after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The increased mortality may be explained by an increased incidence of RCC and metastatic RCC in these patients. In a study of 15 kidney transplant centers in France, the incidence of recurrent RCC after kidney transplant was 9.1% and the 5‐year survival of these patients was 41.7% 36 as compared to 91.4% in kidney transplant population without RCC 37 . In a meta‐analysis of 11 studies, the mortality rate in kidney transplant recipients with RCC was 15.0% at a mean follow‐up of 42 months after RCC diagnosis 38 .…”
Section: Prognosis Of Kidney Transplant Recipients With Cancermentioning
confidence: 99%